Analysis of D-Dimer Levels Based on Histopathological Grading of Breast Cancer - Devita, Yessi; Digambiro, Reza Aditya; Hastuty, Dewi (Jurnal Kedokteran Meditek, 2025)
Background: Breast cancer is the most common malignancy among women worldwide. Systemic activation of coagulation, reflected by elevated D-dimer levels, has been associated with advanced stage, metastasis, and poor prognosis in breast cancer. However, it remains unclear whether D-dimer also correlates with histopathological grade as an indicator of intrinsic tumor aggressiveness, particularly among patients with invasive breast cancer in Indonesia. Objective: To evaluate the association between plasma D-dimer levels and histopathological grading of invasive breast cancer. Methods: This cross-sectional study included 180 untreated female patients with primary invasive breast cancer, comprising 60 cases each of Grade I, Grade II, and Grade III tumors. Plasma D-dimer levels were measured using a latex-enhanced immunoturbidimetric assay, and histological grading was determined according to the Nottingham system. Data were analyzed using the Kruskal–Wallis test, ANOVA on log-transformed values, post-hoc tests, and ANCOVA with adjustment for age, body mass index (BMI), clinical stage, C-reactive protein (CRP), lymphovascular invasion, and molecular subtype. Receiver operating characteristic (ROC) analysis was performed to distinguish Grade III from lower grades. Results: Median D-dimer levels increased progressively from Grade I (501.7 ng/mL) to Grade II (831.0 ng/mL) and Grade III (1312.9 ng/mL), with a statistically significant overall difference (p < 0.001). ROC analysis for identifying Grade III yielded an AUC of 0.960 with an optimal cut-off of 965.5 ng/mL FEU (sensitivity 91.7%, specificity 90.0%). Conclusion: Plasma D-dimer levels are significantly associated with histopathological grade in invasive breast cancer, independent of potential confounders. These findings suggest that D-dimer testing may help identify patients with high-grade tumors at an early stage, thereby refining risk stratification, informing more intensive treatment planning, and raising vigilance for thromboembolic complications, particularly in resource-limited settings.. ctice.